Family Behavior In Caring Patients With Diabetic Foot At Home - Ginting, Daniel Suranta; Tarigan, Mula; Amelia, Rina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Diabetic ulcers are one of the chronic complications of diabetes mellitus. Families are important partners in providing complex health services such as during the treatment of diabetic foot ulcer patients. This study is a qualitative study that aims to explore the meaning of family experiences in caring for diabetic foot ulcer patients at home in Delitua Village. This study uses a phenomenological qualitative method with interviews with families who have experience caring for diabetic foot ulcer patients for more than one year at home. The sampling technique used purposive sampling with ten participants. This research was conducted from December 2020 to February 2021. Data analysis used the Colaizzi method. The results of the study found the themes of family experience in treating diabetic foot ulcer patients, namely (1) emotional experience in treating diabetic foot ulcer patients (2) hard efforts to treat diabetic foot ulcer patients (3) Getting support from family in treating diabetic foot ulcer patients. (4) Experiencing limitations in treating diabetic foot ulcer patients (5) Family expectations in treating diabetic foot ulcer patients. Based on the results of the study, it was found that the family could not provide good care in treating diabetic foot ulcer patients at home.  Abstrak: Ulkus diabetikum merupakan salah satu komplikasi kronik dari diabetes melitus. Keluarga merupakan mitra penting dalam memberikan pelayanan kesehatan yang kompleks seperti selama perawatan pasien ulkus kaki diabetik. Penelitian ini merupakan penelitian kualitatif yang bertujuan untuk menggali makna pengalaman keluarga dalam merawat pasien ulkus kaki diabetik di rumah di Desa Delitua. Penelitian ini menggunakan metode kualitatif fenomenologis dengan wawancara keluarga yang memiliki pengalaman merawat pasien ulkus kaki diabetik selama lebih dari satu tahun di rumah. Teknik pengambilan sampel menggunakan purposive sampling dengan sepuluh orang partisipan. Penelitian ini dilakukan pada bulan Desember 2020 sampai dengan Februari 2021. Analisis data menggunakan metode Colaizzi. Hasil penelitian menemukan tema pengalaman keluarga dalam merawat pasien ulkus kaki diabetik yaitu (1) Pengalaman emosional dalam merawat pasien ulkus kaki diabetik (2) upaya keras merawat pasien ulkus kaki diabetik (3) Mendapatkan dukungan dari keluarga dalam merawat pasien ulkus kaki diabetik. (4) Mengalami keterbatasan dalam merawat pasien ulkus kaki diabetik (5) Harapan keluarga dalam merawat pasien ulkus kaki diabetik. Berdasarkan hasil penelitian didapatkan keluarga dapat belum memberikan asuhan yang baik dalam merawat pasien ulkus kaki diabetik di rumah